ETHICAL AND LEGAL ASPECTS OF INFECTIONS DISEASES AND VACCINATION Part 4. The balance between universal ethical and ecoethics principles on zooanthroponosis - O. I. Kubar (Sankt-Peterburg : NIIÈM imeni Pastera, 2015)
The current paper continued the presentation of the data on ethical, legal and social aspects of the problems connected with the study for prevention infections diseases, additionally including the wide list of infections diseases and increasing the specter of ethical problems in the science in comparision with previous publications in this aria. The investigation of the balance universal ethical principles and ecoethics in the field of zooanthroponosis has been done first time in this paper. Data of the paper are based on the scientific and professional experience of the authors both in infections diseases and bioethics and give the analysis of main international UNESCO documents on bioethics and ecoethics. The principal element that has been used by authors for analysis was the view on epidemiology of zooanthroponosis as ecological process for integration between ethiological agents of infections diseases on the real population of different animals including human beings. Such approach became the base for including the biological, social, economical, topographic and environmental factors for investigation the principals of control and prevention in the aria of zooanthroponosis. In the paper has been presented the set of both environmental principles: common and practical. Theoretical picture of the application the philosophical standards of environmental ethics has been done in real conditions of ethiology, patogenics, epidemiology, clinic, treatment and prevention such kinds of zooanthroponosis as: eastern equine encephalitis, tick borne encephalitis, leptospirosis, Q-fever, tularemia, hemolytic uremic syndrome, listeriosis, West Nile fever, pseudo-tuberculosis and others. In the frame of the understanding ideology and principless of environmental ethics such as “respect for all life forms, human and non-human” and “respect for biodiversity” in the practical situation of zooanthroponosis the priority of prevention human being and responsibility for protection the rights of future generations was shown. The same time the value of bioethical and environmental ethics for control of zooanthroponosis was demonstrated with the justice of such principals as: “safeguarding the sustainability of the biosphere”, “environmental justice”, “precautionary principle” and “Earth as global commons”. In general it was contributed substantially for understanding the necessarily of the balance in using the base principals of bioethics and environmental ethics with the priority of surveillance and control in health care.